Isolation and identification of bacteriocin-producing probiotic lactic acid bacteria from the rainbow trout (Oncorhynchus mykiss): activity against Flavobacterium psychrophilum - Pereira, Wellison Amorim (2023)
The environment has a great influence on the determination of the microbiota of animals. Many of these microorganisms have probiotic potential due to their possible application in various industry segments, such as biotechnological applications. This study aimed to evaluate the biotechnological potential of probiotic bacteria after their application in different animal models. Therefore, the data presented come from an experimental study and the construction of literature reviews. The first study revealed that bacteria isolated and characterized for their safety and antimicrobial activity had positive results and can be considered as candidates for future in vivo studies of probiotic supplementation in animal models. It was observed that the newly isolated strains (Lactococcus lactis L1 and L2 and Enterococcus faecium 135) produced BLIS (antimicrobial substance similar to bacteriocin) with inhibition of several food and aquatic pathogens, mainly Listeria monocytogenes, Salmonella Choleraesuis and Salmonella Typhimurium. All isolates were sensitive to all tested antibiotics (ampicillin, clindamycin, streptomycin, chloramphenicol, rifampicin, gentamicin, vancomycin). In an adhesion test with Caco-2, the strains showed a percentage of adhesion greater than 60%, with no expression of virulence factors (gelatinase and hemolysin) being observed. In resistance tests, EF was resistant to pH 2.5 and 3.0 and EF/L2 was resistant to bile salts. Genes for bacteriocins such as Nisin (L1 and L2) and Enterocin A, B, P and Mundticin KS (EF) were observed. Likewise, the other studies bring a broad and detailed analysis of the main results published in recent years related to the benefits of using probiotics for aquaculture in general, for tilapia farming and for pig farming. Aspects related to the effect on the immune system, growth, resistance to pathogens and stress, among others, were analyzed. Therefore, it was demonstrated that probiotics can be considered for dietary supplementation of in vivo models, being possible auxiliary agents in the control of pathogens and in the promotion of growth, and can be used in the formulation of foods that will also benefit the health of final consumers.